THE EFFECT OF IMPLEMENTING MOTIVATIONAL INTERVIEWING AND TASK-CENTERED TECHNIQUES ON THE TREATMENT OF SUBJECT “GV” WHO ABUSES DRUGS IN THE VILLAGE OF ASIH, CISARUA SUB-DISTRICT - Riani, Danyi (LP2M IAI Al-Khairat Pamekasan, 2025)
The purpose of this study was to obtain an overview of the level of relapse (relapse) in respondents who use drugs, as well as to analyze the effect of the implementation of Motivational Interviewing and Task-Centered techniques on three stages of relapse, namely emotional relapse, mental relapse, and physical relapse. The research method used is quantitative with a single-subject design. Data collection techniques were conducted through observation, unstructured interviews, and documentation studies. The data validity test used the Product-Moment correlation formula, while the reliability test used Alpha Cronbach with the help of the SPSS (Statistical Product and Service Solution) program. Data analysis was conducted using quantitative analysis techniques using the Two Standard Deviation (2 SD) formula to test the main hypothesis and sub-hypotheses. The results showed that the application of Motivational Interviewing and Task-Centered was effective in reducing the relapse rate of respondents with the initials “GV” who abused drugs. In the aspect of emotional relapse, the score before the intervention reached 32 points and decreased to 15 points after the intervention. In the aspect of mental relapse, the score before the intervention amounted to 28 points and decreased to 19 points. Meanwhile, in the aspect of physical relapse, the initial score of 27 points decreased to 16 points after the intervention was conducted. Thus, it can be concluded that the combination of Motivational Interviewing and Task-Centered techniques significantly contributes to suppressing the tendency of emotional, mental, and physical relapse in individuals who use drugs, thus potentially becoming an effective intervention approach in rehabilitation programs.